Kai kurie mokslinės informacijos efektyvumo žemės ūkyje tyrimų rezultatai (pagal užsienio literatūros medžiagą) - Šimkevičius, Julius (Knygotyra, 1974)
In the article in a form of a bibliographic survey some of the foreign books and papers, devoted to problems of agricultural information are critically evaluated. The importance of the agricultural information in introducing new scientific achievements and techniques in the agricultural production to rise its produktivity, is stressed. It is stated, that in some foreign countries with a developed agriculture, more and more attention is paid to problems of a better use of materials of agricultural information, and to the investigation of its effectiveness.